Association between the ACYP2 Polymorphisms and IgAN Risk in the Chinese Han Population - Gang Jin; Yan Liang; Xiaohui Yan; Linping Zhang; Zhenjiang Li; Aiping Yin; Xiaoming Wang; Puxun Tian (Karger Publishers, 2019)
Background/Aims: The association between ACYP2(Acylphosphatase 2) polymorphisms and immunoglobulin A nephropathy (IgAN) risk in the Chinese Han population remains unclear. We aimed to evaluate the association between ACYP2 polymorphisms and IgAN risk by performing a case-control study. Methods: Eleven ACYP2 single nucleotide polymorphisms (SNPs) from 416 IgAN patients and 495 healthy controls were genotyped using the Sequenom MassARRAY platform. Odds ratio (OR) and 95% confidence interval (CI) were calculated to evaluate the association of ACYP2 polymorphisms with IgAN risk. Results: We observed that rs843720 was significantly associated with an increased risk of IgAN (allele G: OR = 1.23, 95% CI: 1.01-1.49, p = 0.036; dominant model: OR = 1.55, 95% CI: 1.01-2.37, p =0.044; log-additive model: OR = 1.43, 95% CI: 1.04-1.95, p = 0.026) before Bonferroni correction. The SNP rs12615793 was also significantly associated with an increased IgAN risk in the recessive model (OR = 3.33, 95% CI: 1.05-10.51, p = 0.042) before Bonferroni correction. Conclusion: These findings suggested that polymorphisms (rs843720 and rs12615793) of ACYP2 may be pivotal in the development of IgAN. However, more functional and association studies with larger sample sizes should be performed to further validate our results in the future.